Re-positioning of Dyna Flowers Landscaping Sdn Bhd in the Landscaping Industry in Kuching/ Agatha Aham Suni … [et. al.] - Suni, Agatha Aham; Tambal, David Kennedy; Tomick, Felex; Abdullah, Ishak; Kundoh, Johny (2003)
Dyna Flowers Landscaping Sdn Bhd (or simply Dyna Flowers) was incorporated in July 1993 and into its ten (10) years on April 10, 2003 and is among the more successful local bumiputra players in the landscaping business. It has a registered office in Kuching. The organisation chart below indicates its lean and mean operations.